Increasing seroprevalence but waning herd immunity against measles after elimination: Longitudinal seroepidemiology of measles in Osaka Prefecture, Japan, 2003–2020. Issue 46 (2nd November 2022) - Kurata, Takako; Miyama, Takeshi; Kanbayashi, Daiki; Kaida, Yuko; Aoyama, Ikuko; Ikemori, Ryo; Banno, Fumiya; Kawahata, Takuya; Mori, Haruyo; Motomura, Kazushi
Highlights: A longitudinal serosurveillance of measles was conducted in Japan from 2003 to 2020. Measles seroprevalence increased in the process to measles elimination. The measles antibody titer decreased after measles elimination. The effective reproduction number became higher toward measles elimination. Measles resurgence due to waning immunity is an issue after the COVID-19 pandemic. Abstract: Japan is one of the countries conducting longitudinal serosurveillance of vaccine-preventable diseases. We conducted surveillance of the local measles-specific antibody titer, calculated the effective reproduction number ( Re ), and compared data of four terms: term 1, 2003–2006 (before the introduction of the second shot of measles-containing vaccine); term 2, 2007–2010 (early term toward measles elimination); term 3, 2011–2014 (later term toward measles elimination); and term 4, 2015–2020 (after elimination of measles in Japan). Approximately 250 sera from volunteers aged 0 to ≥ 40 years were collected and examined for measles-specific IgG using the gelatin particle agglutination (PA) method annually from 2003 to 2020. Seroprevalence and the geometric mean of the PA antibody titer were examined by term. Re was calculated using the age-dependent proportion immune and contact matrix for each term. Of the 4, 716 sera, 886 in term 1, 1, 217 in term 2, 1, 069 in term 3, and 1, 544 in term 4 were collected. The seroprevalence gradually increased from term 1 (88.3% CI 86.0–90.3) to term 4 (95.7% CI 94.6–96.7), and the seroprevalence of term 1 was significantly lower than those of other terms (Fisher's exact test, p < 0.001 ), with PA titer ≥ 16 as positive. By contrast, PA antibody titers significantly decreased from term 1 (median 1, 024) to term 4 (median 256) (Mann–Whitney U test, p < 0.001 ). With the protection level (PA titer ≥ 128 and ≥ 256) as positive, Re gradually increased from term 1 (1.8 and 2.3) to term 4 (2.5 and 4.8, respectively). Waning levels of measles antibodies potentially increase the measles susceptibility in Osaka, Japan. This trend might imply a limitation of vaccine-induced immunity in the absence of a natural booster for wild strains after measles elimination. This study provides a cue for maintaining continuous measles elimination status in the future.